Pola aktivitas harian Leptocorisa oratorius Fabricius (Hemiptera: Alydidae) pada berbagai ketinggian tempat di Daerah Istimewa Yogyakarta - Fanuel Triaswanto; Ultha Rifqy Riswanta; Naufal Urfi Dhiya Ulhaq; Muhammad Luqman Fathoni; RCH Soesilohadi (Perhimpunan Entomologi Indonesia, 2019)
Rice ear bug (Leptocorisa oratorius Fabricus) is a pest insect of rice plants. The daily cycle of L. oratorius is largely unknown. Therefore, this research aims to study the daily activity pattern of L. oratorius at different altitudes within the Special Region of Yogyakarta. The study is done by manually counting L. oratorius at rice paddies that have entered the generative stage. Hourly measurement was made from 06.00 until 18.00 Western Indonesian Time. The rice paddies are located at different altitudes of 40 MASL (Trirenggo, Bantul), 130 MASL (Seyegan and Mlati, Sleman), and 340 MASL (Ngemplak and Pakem, Sleman). Environmental parameters (air temperature, light intensity, and humidity) are also measured at each rice paddy every 15 minutes during the same time span. Data were analyzed was performed to obtain a relationship between environmental parameters in the presence of L. oratorius. Data analysis using regression and correlation analysis. In general, the daily periodicity of L. oratorius has two peaks (06:00–07:00 WIB and 16:00–17:00 WIB) and valleys (11:00–12:00 WIB). Activities commonly found all the time are eating and visiting. Mating activities occur in the morning and taking shelter activities during the day. The air temperature and light intensity factors showed a negative correlation, while the humidity factor showed a positive correlation. No significant differences were found between altitude for periodicity activity patterns and environmental parameters except for the rice field ecosystem at 130 MASL.